Oncoplasty: How to start and experience from Yogyakarta - Herjuna Hardiyanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
AbstractReconstruction surgery after tumor removal is increasingly essential because of changes in patient expectations and demand. With the advance of early screening and detection, our ability to detect early stage cancer is significantly improved. Reconstruction is mostly suitable in patients with early stage cancer. In addition, there is growing ability that that immediate reconstruction in particular selected patients can be performed in a single time operation combining oncological and aesthetic procedures with considerably excellent result. With the implementation of full coverage insurance by BPJS, most oncological surgery including in breast cancer will be performed by general surgeon in regency hospital. Reconstruction in selected patients usually is performed as delayed procedure by plastic surgeon. With the advance in surgical oncology training, breast surgery should be performed by surgical oncologist with specific oncoplasty training that can offer immediate reconstruction with both extensive removal tumor and reconstruction. Therefore, training in oncoplasty is very important for surgical oncologist. In Yogyakarta, we performed reconstruction after surgery of breast tumor, thyroid cancer, radical neck dissection and facial basal cell carcinoma with relatively excellent results. Further training and innovation are required to improve this early stage oncoplasty practice in Yogyakarta.Keywords :